PEMBELAJARAN PRODUKTIF BERBASIS LITERASI DIGITAL PADA MAHASISWA BIPA (BAHASA INDONESIA UNTUK PENUTUR ASING) - Susanti, Elvi; Nurhamidah, Didah (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The Covid-19 pandemic has led to all forms of digital-based learning. All formal education institutions organize online learning, including BIPA students. This causes the use of technology to increase. BIPA students using technology not only seek academic information about the Indonesian language, but also get to know Indonesian culture. One of the references for measuring the level of digital literacy is the Bawden Conception, which divides it into four aspects, namely basic digital literacy skills, background knowledge of information, digital literacy main competencies, and attitudes and perspectives of information users. The method used is descriptive research that uses a quantitative approach. The form of a movement to encourage productive learning based on digital literacy is that BIPA students can compile an article by including several references.